Successful laparoscopic management of accessory cavitated uterine mass: a rare case - Pratapwar, Dinesh D.; Zunjare, Sarika Pramod; Tasneem, Fasiha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Accessory cavitated uterine mass (ACUM) is a rare and unique congenital anomaly. The dysmenorrhea presented by these patients is almost never resolved by any medications but only by surgical line of management. Herein, we are discussing a case of ACUM who had medically refractory dysmenorrhea and treated by laparoscopic excision and repair. ACUM is the newly identified popping up cause of dysmenorrhoea requiring surgical line of management only. Fewer than 40 cases, worldwide, have been reported in the literature with the youngest case being a 13-year-old girl. Laparoscopic excision has shown good postoperative results. Dysmenorrhea is a significant cause of reduced quality of life. High degree of suspicion, early investigations and identification of such cases help in appropriate management and reduce the duration of symptoms and thus the seamy side of life can be made better.